Biomassa dan bioarang dari limbah kotoran kuda tanpa dan dengan perlakuan menggunakan sodium hidroksida: studi nilai kalor dan kadar abu - Padang, Y. A.; Sari, N. H.; Nurchayati, N.; Triadi, A.A. A.; Sutaryono, Y. A.; Muharman, M. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2020)
This study aims to determine and test the characteristics of horse feces briquettes without and with NaOH treatment as an alternative fuel. The experiment has been carried out in a laboratory. Biomass has been treated with 8% NaOH for 2 h, and has been compared with untreated biomass briquettes. Characterization of the calorific value and ash content of biomass briquettes and bio charcoal briquettes have been investigated. The results showed that the heat value for briquette samples after being treated increased in the range of 4894.6 cal/g – 5855.16 cal/g, while the ash content decreased in the range of 39% to 49.44%; this is caused by a decrease in non-lignocellulosic of horse feces content. It can be concluded that the horse feces biomass briquette with NaOH treatment can be an alternative fuel to replace the skin and leaf briquettes.